Penerapan Manajemen Mutu dalam Meningkatkan Prestasi Anak Usia Dini di Tadika Didik Bistari Gemilang, Malaysia - Liyana Adriana; Syahrul Amsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the implementation of quality management implemented by Tadika Didik Bistari Gemilang in improving the achievement of early childhood. This research uses a qualitative descriptive method applied in this research through data collection techniques, namely observation, interviews and documentation. The results of this research show that in implementing quality management in improving early childhood achievement, researchers used 4 aspects, first, the education program offered at Tadika Didik Bistari Gemilang was adapted to the National Pre-School Standard Curriculum (KSPK) with the concept of integrated learning. The learning process is carried out using easy and fun methods, one of which is learning while singing and playing. Second, the Parenting and Care Program, which provides security, food, sleep, bathing and care from the time the children arrive until they return home. In the morning, the teacher welcomed the children and asked them to eat the morning snacks provided earlier. Third, infrastructure This can be seen from the condition of the safe, comfortable, clean, complete facilities, many toys that can be played before learning, as well as learning tools and media used to train students' focus and motor skills. And fourth, competent teachers to run and optimize educational programs and care and maintenance programs well, of course, the role of competent teachers is needed.